Journalistic framing on abortion in Peru (2015-2019): a comparative analysis between the press of the metropolitan Lima and Piura regions - García Romero, Enrique (2021)
This article shows the results of an academic research on the way in which the Peruvian press addresses the issue of abortion. A content analysis has been carried out to detect the frames, themes and journalistic sources present in 160 texts published during the five-year period 2015-2019 by the newspapers El Comercio, Perú 21, La República, La Hora, Correo and El Tiempo. The first three are part of the most read press in the metropolitan Lima region, while the last three are among the most read newspapers in the Piura region. These two regions are the most populated in the Andean country. One of the variables of the content analysis are the generic frames used by the press: pro-life, pro-abortion and neutral/ambiguous. The results show that five of the six selected newspapers –all except El Comercio– used mostly pro-life frames, that is, opposed to induced abortion. On the other hand, the three newspapers that are part of the most read press in the Piura region used more pro-life frames in percentage terms than the three newspapers that are part of the most read press in the metropolitan Lima region. Regarding the type of sources that journalists used to report on abortion, they mostly belong to the political and religious spheres, while those from the scientific sphere were relegated to third place.